Heterolithic Thin Bedded Reservoirs Volumetric Estimation, Quantification and High-Resolution 3D Modelling - Kampit, Stanley Jaul; Tuan Muda, Tuan Zaid; Kamaruddin, Samira Albati; Abdullah Anas, Zulkarnain; Mohd Azam, Mohd Nor Hisham (Journal of Advanced Research in Applied Mechanics, 2020)
The heterolithic thin-bedded sand and shale are very commonly associated reservoirs column in shallow water clastic depositional environment in Malaysia Basin. The complexity in reservoirs characterization of heterolithic thin-bedded sand often leads to underestimating the potential contribution of these types of the reservoir for development and exploration targets. The naturally laminated of heterolithic thin-bedded sand make it more difficult in building the realistic 3D geological model and has an impact on volumetric calculation and reserve estimation. This study is applied in the development phase by introducing Log resolution enhancement methods in laminated thin-bedded sand characterization to quantify the reservoir potential with high-resolution 3D modelling methods. The quantification of sand and shale in thin bedded analysis using core data and image logs, then transform into lithofacies classification from sand and shale volume cut-off. The distribution and computation of lithofacies and reservoir properties build into a 3D model is obtained from a geological depositional environment analog at field-scale of a conventional setting. The results indicated high-resolution 3D geological modelling successfully preserved the characterization of thin-bedded sand and shale; and revealed an excellent correlation with the image log. The presence of inter-bedded sand and shale of reservoir column in the 3D geological model provides the quantification of thin-bedded sand contribution and potential realistic volumetric estimation for the entire reservoir interval. The thin-bedded reservoir characterization and high-resolution 3D modelling technique successfully address the existent of heterolithic reservoir facies previously simplified.